Citogenética comparativa entre ictiofáunulas isoladas por um divisor de águas em regiões limítrofes de duas bacias hidrográficas na Serra da Mantiqueira - Centofante, Liano (Universidade Federal de São Carlos, 2003)
The Serra da Mantiqueira is located in the southeastern region of Brazil, and is a landmark for the political division between the São Paulo and Minas Gerais States, serving as an effective water divisor for the Paraíba do Sul and Paraná Rivers. This way, the Serra da Mantiqueira may act as an expressive biogeographic barrier for the isolation of the ichthyofaunas of these hydrographic basins. The present work was carried out with ten fish species (Characidium gomesi, C. cf. zebra, C. lauroi, C. cf. alipioi, Parodon sp., P. tortuosus, Astyanax fasciatus, A. parahybae, Hyphessobrycon anisitsi e Rhamdia sp.), belonging to four distinct families, representing the ichthyofaunas of this limiting region between some tributaries of the Paraíba do Sul River and some drainage rivers of the Sapucaí River, Paraná basin. The cytogenetic studies aimed the chromosomal characterization and the comparative analysis between the species of these ichthyofaunas. Among the main results obtained in the present work, we highlight: the karyotypical descriptions of the ten species previously mentioned; the discovery of a new species for the genus Parodon; the description of three new ZZ/ZW sex chromosome systems; and the discovery of two new cases of natural triploidies, one of them being associated to the B chromosome. The studies also permitted the formulation of hypotheses on the possible causes of the origin of the chromosome diversity found in the species of this region, the verification of the role the Serra da Mantiqueira has in the isolation and biogeographic distribution of the ichthyofaunas involved, and also the correlations between the species of the two hydrographic basins.
Keywords: Genética animal; Ictiofauna de riachos; Citigenética; CIENCIAS BIOLOGICAS::GENETICA